2009
DOI: 10.1177/0309132509351042
|View full text |Cite
|
Sign up to set email alerts
|

Geographies of toponymic inscription: new directions in critical place-name studies

Abstract: The study of place naming, or toponymy, has recently undergone a critical reformulation as scholars have moved beyond the traditional focus on etymology and taxonomy by examining the politics of place-naming practices. In this article, we provide a selective genealogy of the ‘critical turn’ in place-name studies and consider three complementary approaches to analyzing spatial inscription as a toponymic practice: political semiotics, governmentality studies, and normative theories of social justice and symbolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
205
0
17

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(222 citation statements)
references
References 75 publications
0
205
0
17
Order By: Relevance
“…For example, place names have in the past been transferable in colonial/historical exploration. More recently, Rose-Redwood et al (2010) have identified how the American military have used existing US toponyms to make the unfamiliar streets, districts, and landmarks of Iraq more manageable. In such instances, these places often bear little if any resemblance to the original locations, although this is not always the case.…”
Section: Transferablementioning
confidence: 99%
See 1 more Smart Citation
“…For example, place names have in the past been transferable in colonial/historical exploration. More recently, Rose-Redwood et al (2010) have identified how the American military have used existing US toponyms to make the unfamiliar streets, districts, and landmarks of Iraq more manageable. In such instances, these places often bear little if any resemblance to the original locations, although this is not always the case.…”
Section: Transferablementioning
confidence: 99%
“…In calls to expand the horizons of critical place name studies Rose-Redwood et al (2010) highlight a need to move beyond rather formulaic debates, in which discussions surrounding power, politics, and resistance routinely come to the surface. They suggest that the commodification of place naming is one underexplored area deserving of greater enquiry.…”
Section: Critical Perspectives On Toponyms As Brand Namesmentioning
confidence: 99%
“…This practice has been termed "toponymic cleansing". 31 Such renaming is "an act of political propaganda with immense proclamative value and public resonance" 32 : it makes an immediate statement that public memory is changing, and is relatively quick and simple to implement. Renaming was intended to decommemorate the communist past and also to 'place' a new narrative of national history and memory into public space.…”
Section: Erasing the Commemorative Landscape Of Communismmentioning
confidence: 99%
“…We know most of geographical names in Hannan district have water features, and the distribution of various types of geographical names in Yingcheng County are much uniform, therefor the information entropy of Hannan District is low and the Yingcheng County is high. From Table 8 we can see the diversity of geographical names which are affected by all of natural landscape, cultural relicts and architectures and so on [41][42][43][44]. Sweeney used place names to interpret floodplain connectivity in the Morava River [45].…”
Section: Information Entropy Calculationmentioning
confidence: 99%